Exploring the current practice of local knowledge management among the Minangkabau community leaders in Agam District, Indonesia for sustainable development / Elva Rahmah ... [et al.] - Rahmah, Elva; Mohamed Shuhidan, Shamila; Wan Yahaya, Wan Aida; Rahman, Mohd Saiful; Marlini, . (Faculty of Information Management, 2023)
Local knowledge is the knowledge found in local communities that consists of a set of experiences that have been accumulated and provides information that shows the local community or local culture's behavioral characteristics. However, studies found that Local knowledge, which has historically been transmitted from generation to generation by word of mouth, is at risk of being lost and the information contained in local knowledge is still not recorded and well managed efficiently. This paper aims to explore the current practice of local knowledge management among the Minangkabau Community leaders in the Agam district, Indonesia for sustainable development focusing on the critical issues, and concrete practices, in local knowledge management. The design is a qualitative analysis based on a detailed case study of the local knowledge management practices in the Agam district, Indonesia with 12 community leaders. The practice of local knowledge management among the Minangkabau Community leaders through three categories, namely input, process, and output local knowledge. Input is special local knowledge from culture and heritage, where knowledge from the contributor consists of tacit and explicit knowledge of the Minangkabau community. The process is the system that emphasizes the complex relationships between knowledge transfer actors and the coexistence of implicit and explicit knowledge transfer mechanisms. The last part of local knowledge management is the output of local knowledge protection.